Vitamin E-inspired multi-scale imaging agent. Issue 1 (1st January 2019) - Ghelfi, Mikel; Maddalena, Lucas A.; Stuart, Jeffrey A.; Atkinson, Jeffrey; Harroun, Thad A.; Marquardt, Drew
Graphical abstract: Abstract: The production and use of multi-modal imaging agents is on the rise. The vast majority of these imaging agents are limited to a single length scale for the agent (e.g. tissues only), which is typically at the organ or tissue scale. This work explores the synthesis of such an imaging agent and discusses the applications of our vitamin E-inspired multi-modal and multi-length scale imaging agents TB-Toc ((S, E)-5, 5-difluoro-7-(2-(5-((6-hydroxy-2, 5, 7, 8-tetramethylchroman-2-yl) methyl) thiophen-2-yl) vinyl)-9-methyl-5H-dipyrrolo-[1, 2-c:2', 1'-f][1, 3, 2]diazaborinin-4-ium-5-uide). We investigate the toxicity of TB-Toc along with the starting materials and lipid based delivery vehicle in mouse myoblasts and fibroblasts. Further we investigate the uptake of TB-Toc delivered to cultured cells in both solvent and liposomes. TB-Toc has low toxicity, and no change in cell viability was observed up to concentrations of 10 mM. TB-Toc shows time-dependent cellular uptake that is complete in about 30 min. This work is the first step in demonstrating our vitamin E derivatives are viable multi-modal and length scale diagnostic tools.